Covert Inequity : Gender Discrimination through Occupational Categorization. - Koerten, Jared (My University, 2009)
Economists have widely recognized and published the importance of gender as a determinant of an individual's wage. Existing policies, however, aim at ensuring that women are paid equal wages as individuals on a case-by-case bases. Our research indicates that this approach may miss larger trends in wage differentials between men and women. Our findings indicate that occupations consisting mainly of females earn less than those that are male-dominated, and these wage discrepancies are increasing over time.
Color poster with text, tables, and graphs.
Keywords: Wages--United States--Sex differences; Wages--United States--Sociological aspects; Occupations--United States--Sex differences; Professions--United States--Sex differences; Posters